THE COLOURED WOMEN’S CLUB OF MONTREAL, 1902-1940: African-Canadian Women Confronting Anti-Black Racism - Este, David; Sato, Christa; McKenna, Darcy (Canadian Social Work Review / Revue canadienne de service social, 2017)
To date, there is limited literature documenting contributions of people of African descent to Canadian social welfare history. Based on both secondary and archival sources, we critically explore from anti-Black racism and African-Canadian feminist per\spectives, the contributions of the Coloured Women’s Club of Montreal (CWCM) from 1902-1940 to the social well-being of Montreal’s Black community. The CWCM played a major role as one of the leading supports for members who encountered harsh challenges in a society where racism prevailed and opportunities for men and women were severely restricted. Club members organized several events that enabled community members to survive in an environment that was hostile to people of African descent, therefore becoming a “pillar of strength” that fostered a stronger sense of community among Blacks living in Montreal. We contend that through their contributions during this time period, these African-Canadian women emerged as key players in the community and secondly, as early social welfare practitioners. It is imperative for social workers to acknowledge the contributions of the women who were involved in the CWCM as a means of interrupting the historical narratives shaping our profession that have predominantly been told from the perspectives of a hegemonic, white culture.